The Dynamic Influence of Religiosity and Knowledge Mediated by Attitude on Consumer Intentions to Buy Halal Products in Indonesia - Sani, Ageng Asmara; Sakifah, Sakifah; Hidayat, Deny (Universitas Alma Ata, 2025)
Introduction : This study examines the dynamic influence of religiosity and knowledge, mediated by attitude, on consumer intentions to buy halal products in Indonesia, where the growing Muslim population has increased the demand for halal goods. Understanding the factors that shape this intention is essential for building consumer trust and strengthening the development of the halal sector. The research addresses how religiosity and knowledge affect purchase intention for halal products, with attitude acting as a mediating variable. This paper contributes by testing the indirect impact of religiosity and knowledge on purchase intention through attitude, a relationship that has not been fully examined in the Indonesian halal consumption context.Methodology: A quantitative method was applied using data from 180 respondents in six provinces across Java. Structural Equation Modeling (SEM) was conducted using LISREL, with Confirmatory Factor Analysis (CFA) employed for model validation.Results: Religiosity and knowledge influence purchase intention only indirectly through attitude (T = 2.56 and 2.87), while attitude itself has a direct significant effect (T = 3.79). Goodness-of-fit indices indicate a well-fitting model (GFI = 0.90, RMSEA = 0.051, Chi-Square = 165.64, df = 113).Conclusion: Attitude plays a critical mediating role between internal values and consumer intention. Stakeholders should focus on strengthening consumer attitudes through education and value based campaigns to boost halal product adoption.